A Microanalysis of Employee Retention Strategies: The Case of Selected Convenience Stores and Their Practices - Xavier Lawrence D. Mendoza; Jerico B. Tadeo; Reychelle T. Bulan; Samuel Jr. B. Leyson; Veronian P. Rodriguez (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
Maintaining top-tier personnel is difficult for convenience stores, as they must compete against larger businesses with higher budgets and more employee advantages. This study aimed to determine the employee retention management practices in selected convenience stores in Cavite, Philippines. It utilized a descriptive research design and convenience sampling technique to select the respondents. The data was acquired by utilizing self-constructed questionnaires and Likert-scale to determine the effectiveness of employee retention. The study found that most respondents who manage a convenience store have 1 to 9 employees, have been operating for 6 to 8 years, and were small enterprises. The study found that variables such as employee compensation, physical working environment, employee growth, engagement, and employee support were highly effective in retaining employees. The researchers recommend that employees seek a good organization that listens to them and cares about their general well-being. Respectively, managers and/or owners should develop efficient and effective strategies to retain and manage employees in a sustainable manner.